Quality by Design and Evaluation of Crosslinked Chitosan Microspheres for the Controlled Delivery of Doxycycline Hyclate - Yadav, Sarita K.; Khan, Gayasuddin; Bonde, Gunjan V.; Bansal, Monika; Mishra, Brahmeshwar (Drug Delivery Letters, 2018)
Background: Periodontitis is chronic bacterial induced infection capable of destroying tooth supporting tissues leading to pain, inflammation and tooth loss. Objective: The objective of the study was to optimize and evaluate Doxycycline Hyclate (DX) entrapped crosslinked chitosan microspheres by employing quality by design (QbD) for the treatment of periodontitis. Methods: Plackett-Burman Factorial Design was applied, and screening of significant factors was done by Pareto, half-normal and main-effect plots. The optimized batch was evaluated for FTIR, XRD, SEM, in-vitro drug release, swelling, and mucoadhesion. Cytocompatibility, antimicrobial, and stability studies were performed to prove its safety, efficacy and long-term utility respectively. Results: The responses like particle size, entrapment efficiency, and time for 80% of drug release was optimized at 75.45 μm, 88.87 % and 10.41 days respectively. FTIR reaffirmed formation of crosslinked microspheres. XRD plots indicated conversion of crystalline DX into amorphous form within microspheres. SEM evidenced spherical microspheres with smooth surfaces. Optimized microspheres showed slow and extended release for about fourteen days. Moreover, chitosan-vanillin (CSV) microspheres exhibited slow swelling with high mucoadhesion attributed to its high hydrophobicity and low degree of crosslinking than chitosan-glutaraldehyde (CSG) microspheres. SRB assay demonstrated high cytocompatibility of CSV than CSG microspheres against L929 cell lines. The optimized microspheres maintained a significant zone of inhibition against Staphylococcus aureus and Escherichia coli growth and showed prolonged stability for use. Conclusion: CSV microspheres showed great potential for their utility in chronic infections such as periodontitis by providing controlled and prolonged delivery of DX.
Keywords: periodontitis